Enhancement of Teachers' Knowledge in Gamification for Improving Reading Skills in Students with Autism Spectrum Disorder - Kurniawan, Agung; Ariesaka, Kiky Martha; Fukata, Editya; Wijaya, Andreas Budi; Putri, Angelica Igsanti; Prasetya, Ahmada Viosepta; Devi, Athaayaa Nastiti Ulayya (Universitas Negeri Malang, 2024)
Autism Spectrum Disorder (ASD) is a developmental disorder characterized by challenges with social interaction, communication, and repetitive behaviors. Students with ASD often struggle with reading skills due to deficits in language comprehension, attention, and social communication. Gamification, applying game-design elements in non-game contexts, has emerged as a promising approach to enhance learning for these students. This study aimed to develop and implement a gamification-based learning application to improve the reading skills of students with ASD in special schools. The initiative sought to empower teachers through comprehensive training and support, enabling them to effectively use gamified educational tools. The method followed the ADDIE model: Analysis involved a needs assessment; Design included creating a training program and evaluation instruments; Development involved creating training materials and preparing for pilot testing; Implementation included conducting the training for teacher and administering pre-tests and post-tests; Evaluation consisted of analyzing test data and feedback. The training session was conducted on July 17, 2024, at SLB Autis Lab UM. Paired t-test results showed a significant increase in mean scores from pre-test (78.67±11.87) to post-test (88.00±10.14), with a P-value of 0.014, indicating effective training. Participant feedback highlighted the gamification application’s appealing interface, ease of use, and positive impact on student motivation, participation, and reading skills. The gamification-based learning application effectively improves reading skills in students with ASD and enhances teachers’ knowledge and skills in using such tools. Ongoing support and professional development for educators are crucial for integrating innovative tools into teaching practices, fostering academic success and overall development for students with ASD.